Development of world oil refining in the context of the coronavirus pandemic - A. P. Solomonov (Вестник университета)
The article is devoted to the analysis of the changes that are taking place in the global oil refining industry under the influence of the current recession in the world economy. Despite the recovery of the global economy after the pandemic, nevertheless, the risks of an intensification of the geopolitical conflict have led to an unprecedentedly difficult situation in the energy markets. Newly emerging restrictions in international trade, including in the form of sanctions, have led to risks of unstable development of the oil refining industry. In turn, the uncertainty in the dynamics of world oil prices, as shown in the article, as well as the trends in the transition to a low-carbon economy, make it difficult to predict the development of the oil and gas industry, including oil refining. The serious changes observed in the structure of fuel production and consumption in the United States will have a significant impact on the development of the industry under study in the future, where there is already a shortage of refining capacity and unstable dynamics of prices for petroleum products. The introduction of additional capacities in the world oil refining, as noted in the article, will not have a significant positive impact on the oil product markets in the short term.